Catholic Integralism Remains Unjust: A Reply to Pink - Vallier, Kevin (American catholic philosophical quarterly, 2025)
Catholic integralists hold a puzzling view about religious coercion: while they agree that forcing the unbaptized into faith violates human dignity, they claim the Church may authorize states to coerce the baptized to retain their faith. In response to my "justice argument" that baptism cannot transform religious coercion from unjust to just, Thomas Pink draws on the distinction between coactio (force against an unwilling person) and coercitio (legal direction educating those receptive to truth). I present three objections to Pink’s response: baptism does not reliably track the educability of the will, identifying educable wills faces insurmountable practical barriers, and the Church lacks authority to delegate physical coercion for religious ends. I conclude that Catholic integralism remains unjust, as it allows impermissible coercion of the baptized.